Fostering trust and understanding in social and healthcare services with migrant-origin parents: qualitative focus-group interviews of foreign-born mothers living in Finland - Kankaanpää, Saija-Liisa (SPRINGER, 2025)
Migrant-origin families may have a pronounced need for psychosocial support and healthcare services, but they face barriers in using services. To ensure the timely use of services, it is important that families understand how service systems work and trust care providers. Thirty-two migrant-origin mothers living in Finland participated in five focus-group interviews and shared their wishes for social and healthcare professionals on how trust and understanding can be increased. The data were analyzed with Qualitative Content Analysis. We identified six main themes related to the use of services and professionals' behavior. These were the need for professionals to justify and explain questions, to meet each family as individuals, the importance of non-verbal communication, the need to talk about racism and discrimination, the importance of cultural sensitivity in services, and a discussion of positive aspects of life after migration and children`s strengths. To foster trust and mutual understanding in social and healthcare services, professionals should be aware of potential cultural differences in family life, while avoiding pre-conceived ideas. Misunderstandings can rise from language barriers and unclear or intimidating questions. It is important that professionals explain what they do and justify why they might inquire about a family's personal matters. Working with interpreters is necessary when professionals and parents do not share a common fluent language. Professionals should also pay attention to their non-verbal communication and to being friendly. Finally, it is important to show interest in families' experienced hardships such as racism as well as their strengths.